2006
DOI: 10.2166/wqrj.2006.025
|View full text |Cite
|
Sign up to set email alerts
|

Million Dollar Arsenic Removal Plants in West Bengal, India: Useful or Not?

Abstract: The effectiveness of arsenic removal plants (ARPs) to provide safe water was evaluated based on a study of 577 ARPs out of 1900 installed in 5 arsenic-affected districts of West Bengal, India. Out of 577, 145 (25.1%) were found in defunct condition. Both raw and filtered water from 305 ARPs were analyzed for total arsenic concentration. Forty-eight ARPs were installed despite raw water arsenic concentrations below the Indian standard (50 µg/L) and in 22 cases even below the WHO guideline value (10 µg/L). Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 13 publications
3
29
1
Order By: Relevance
“…We found most of the arsenic removal units from various manufacturers are technically sound. But our follow-up studies of the filters installed in many affected villages showed most of them were not functioning [47,48] due to poor maintenance and less people's participation. We have observed that these systems work if the owners regularly clean the domestic filter and back wash the ARP.…”
Section: Managing Future Danger Of Arsenic In Bangladeshmentioning
confidence: 89%
“…We found most of the arsenic removal units from various manufacturers are technically sound. But our follow-up studies of the filters installed in many affected villages showed most of them were not functioning [47,48] due to poor maintenance and less people's participation. We have observed that these systems work if the owners regularly clean the domestic filter and back wash the ARP.…”
Section: Managing Future Danger Of Arsenic In Bangladeshmentioning
confidence: 89%
“…Arsenic removal technologies were reviewed ( [9,26,27,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]576]). The major arsenic removal technologies are compared in Table 2.…”
Section: Major Coagulation/coprecipitation Technologies Advantages DImentioning
confidence: 99%
“…Household-based filters and low-arsenic dug wells require significant maintenance (1, 2), pond water is too polluted for purification by sand filters, and rainwater harvesting is seen as a solution only during monsoon (2). Treatment plants for shallow groundwater have been constructed in some areas, but a survey of 577 high-cost facilities in West Bengal, India, indicates that 82% are ineffective (3). Piped water systems that tap low-arsenic groundwater supplies are a preferred alternative, although the higher cost and maintenance effort may reduce their appeal (2).…”
mentioning
confidence: 99%